(untitled) (World Bulletin of Management and Law, 2022)
This article is devoted to the characteristics of the concept of "labor discipline", "disciplinary offense", "disciplinary responsibility". The article reveals their main features and characteristics, as well as the types of disciplinary measures applied in the Republic of Uzbekistan. The analysis of the legislation of foreign countries in this area is carried out. In addition, this article contains provisions on problematic procedures for bringing an employee to disciplinary liability under the labor legislation of the Republic of Uzbekistan and makes proposals on the need for amendments and additions to the current legislation in the field of employee disciplinary liability